2020
DOI: 10.1007/s10803-020-04618-w
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Autism Symptoms Prior to 18 Months of Age: A Systematic Literature Review

Abstract: Pre-diagnostic intervention for autism spectrum disorder (ASD) allows symptoms to be addressed as they emerge, often between six to 18 months, rather than after the full onset of the disorder. A systematic literature review, spanning the previous six years was conducted in order to provide an updated review looking at the earliest behavior symptoms of ASD. All included studies used a prospective experimental design, reported on symptoms that emerged before 18-months of age, exclusively in children who would la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 84 publications
2
47
0
1
Order By: Relevance
“…Research has demonstrated that at the age of 6 months behavior of children later diagnosed with ASD is similar to that of typically developing children [ 50 , 118 , 119 ]. ASD’s signs of impaired social interaction and communication slowly emerge in the second half of the first postnatal year to become more evident in the beginning of the second year [ 50 , 119 , 120 , 121 ]. With increasing age the majority of children with ASD gradually loose social and communicative abilities that they had mastered previously [ 119 ].…”
Section: Early Detection Of Developmental Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has demonstrated that at the age of 6 months behavior of children later diagnosed with ASD is similar to that of typically developing children [ 50 , 118 , 119 ]. ASD’s signs of impaired social interaction and communication slowly emerge in the second half of the first postnatal year to become more evident in the beginning of the second year [ 50 , 119 , 120 , 121 ]. With increasing age the majority of children with ASD gradually loose social and communicative abilities that they had mastered previously [ 119 ].…”
Section: Early Detection Of Developmental Disordersmentioning
confidence: 99%
“…With increasing age the majority of children with ASD gradually loose social and communicative abilities that they had mastered previously [ 119 ]. Examples of specific early signs are deficits in joint attention, gazing at faces and orienting to their name being called [ 50 , 118 , 121 ]. An unspecific sign of ASD in infancy is atypical emotionality and self-regulation [ 88 , 122 ].…”
Section: Early Detection Of Developmental Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Regression is understood in AIM as the final point of a pre-encephalopathy process. The pathway to chronicity is considered to be an individual process and not a single event [63] and the final point could be considered to be the regression. The chronic status of the encephalopathy would be related to chronic pathophysiological processes in the brain in ASD (see reference [52] for further explanation).…”
Section: The Controversy About Whether a Static Or Dynamic Encephalopathy Contributes To Asdmentioning
confidence: 99%
“…This special issue includes four studies (Hatch et al 2020;Lorenzo et al 2020;Stenberg et al 2020;Tanner and Dounavi 2020) that provide new insight on early emerging symptoms. This is a critical area of investigation because the age of diagnosis in epidemiological samples is still 3-5 years of age (Baio et al 2018;Fountain et al 2011;Mandell et al 2010;Shaw et al 2020).…”
Section: Early Manifestations and Outcomes Of Children Identified Earliermentioning
confidence: 99%